Perspectives on rapid fentanyl test strips as a harm reduction practice among young adults who use drugs: a qualitative study - Jacqueline E. Goldman; Katherine M. Waye; Kobe A. Periera; Maxwell S. Krieger; Jesse L. Yedinak; Brandon D. L. Marshall (BMC, 2019)
Abstract Background In 2016, drug overdose deaths exceeded 64,000 in the United States, driven by a sixfold increase in deaths attributable to illicitly manufactured fentanyl. Rapid fentanyl test strips (FTS), used to detect fentanyl in illicit drugs, may help inform people who use drugs about their risk of fentanyl exposure prior to consumption. This qualitative study assessed perceptions of FTS among young adults. Methods From May to September 2017, we recruited a convenience sample of 93 young adults in Rhode Island (age 18-35 years) with self-reported drug use in the past 30 days to participate in a pilot study aimed at better understanding perspectives of using take-home FTS for personal use. Participants completed a baseline quantitative survey, then completed a training to learn how to use the FTS. Participants then received ten FTS for personal use and were asked to return 2-4 weeks later to complete a brief quantitative and structured qualitative interview. Interviews were transcribed, coded, and double coded in NVivo (Version 11). Results Of the 81 (87%) participants who returned for follow-up, the majority (n = 62, 77%) used at least one FTS, and of those, a majority found them to be useful and straightforward to use. Positive FTS results led some participants to alter their drug use behaviors, including discarding their drug supply, using with someone else, and keeping naloxone nearby. Participants also reported giving FTS to friends who they felt were at high risk for fentanyl exposure. Conclusion These findings provide important perspectives on the use of FTS among young adults who use drugs. Given the high level of acceptability and behavioral changes reported by study participants, FTS may be a useful harm reduction intervention to reduce fentanyl overdose risk among this population. Trial registration The study protocol is registered with the US National Library of Medicine, Identifier NCT03373825, 12/24/2017, registered retrospectively. https://clinicaltrials.gov/ct2/show/NCT03373825?id=NCT03373825&rank=1